Caribbean security on the eve of the 21st century - Griffith, Ivelaw L. (Institute for National Strategic Studies WashingtonUS, 1996)
Provides a balanced account of the events in the relationship during the later years of the Cold War. Discusses the impact of the Cold War on the US-Caribbean security relationship. Shows also how the end of the Cold War has fundamentally changed the way we view not only security, but also each other as partners in an emerging interdependent security relationship.